Patient and Community Attitudes toward Perioperative Biobanking and Genomic Research. Issue 3 (May 2017) - Liddell, J.; Bain, C.; Myles, P. S.
We surveyed hospital patients and clinicians to ascertain their attitudes to the establishment of a perioperative biobank for future genomics research, and whether the requirements for an opt-out approach to consent can be met. We enrolled hospital patients (n=187), patient spouse/family members (n=64), ethics committee members (n=14), clinical staff (doctors and nurses [n=67]), and unspecified community members (n=10). They were asked to rate and describe their views on medical research and biobanking, the need for individual consent, and the importance of confidentiality. Of 406 survey forms distributed, 342 (84%) were returned. Nearly all participants (98%) indicated that a perioperative biobank is important, 93% were comfortable with de-identified genetic research, and 90% indicated that the hospital should be able to use leftover blood for medical research, provided the research has been approved by an ethics committee and personally identifying information has been removed. Participants were more likely to support biobanking if it used de-identified samples, and if, for this reason, their consent was not sought. Participants with chronic medical and surgical conditions were significantly more supportive and comfortable with genetic research, as were most in the hospital community. Most hospital patients, community members and clinicians are supportive of the development of a perioperative biobank used for genomic research. This supports the adoption of an opt-out approach to consent model.